Unveiling the Role of Mackinawite and Fe 0 Components in Arsenic(III) Removal by Sulfidated Zero-Valent Iron under Aerobic Conditions - Cai, Shichao; Zhao, Jiawei; Tan, Yurou; Wu, Zhongkuan; Chen, Bo; He, Feng (Environmental science & technology, 2025)
In this study, we synthesized microscale sulfidated zerovalent iron (S-mZVI) with controllable mackinawite (FeS) content up to nearly 100 wt % and investigated the roles of FeS and Fe for arsenite (As(III)) sequestration under aerobic conditions. Batch experiments show that FeS and Fe contents determine the kinetics and longevity of As removal by S-mZVI, respectively. The Fe /FeS galvanic cell accelerates the consumption of Fe by dissolved oxygen (DO) while preserving FeS to preferentially remove As as sulfide, which is protected from oxidation by Fe . In column studies, mZVI and S were mixed in sand to form S-mZVI in situ. Results of sequential extraction of reacted S-mZVI particles from different column zones and run stages further indicate that As formed as sulfide by S-mZVI, which was then oxidized by DO after Fe depletion to form As-iron (hydr)oxides. X-ray absorption near-edge structure characterization confirmed that As sulfide is mainly in the form of realgar (As S ). S-mZVI (2 wt % of column sand) reduces total As from 2 mg/L to 10 μg/L, up to 300 bed volumes, with a residence time of 70 min. In situ synthesis and cost advantages make S-mZVI a promising method to address As contamination issues worldwide.